The Effects of Virtual Algebra Tiles on the Performance of Year 8 Students in Solving Algebraic Linear Equations - Alias, Nurul Hafizah; Shahrill, Masitah; Nurhasanah, Farida; Adnan, Mazlini (EDUPEDIA Publisher, 2024)
This study aims to examine the effects of Virtual Algebra Tiles (VAT) on the performance of 41 Year 8 students in solving algebraic equations. The VAT used in this research is accessible and free through a website called Didax. Quantitative and qualitative data were collected from Class 8X (21 students) and Class 8Y (20 students) through convenient sampling in a public secondary school. The Didax VAT was used as an intervention tool to aid students in solving algebraic equations. Quantitative data, in the form of pre-test, post-test, and questionnaire, was administered to the students and analysed to determine the statistical significance of the findings. Qualitative data were used in focus group interviews to explore students’ perceptions of Didax VAT further. The conclusions of this study indicated that the result of the paired sample t-test was not significant, the intervention had a small positive effect on student learning. The qualitative data revealed most students positively perceived using Didax VAT in their learning.